Seizure of Local Community Land: Case Study on the Negative Impact of Firestone's Involvement in Liberia - Susi, Neng; Mahdi, Imam (Borong Newinera Publisher, 2024)
Land seizure by foreign investors in Liberia can pose a threat to the individual security of local communities. This research employs a descriptive qualitative method with a case study approach to explore the impact of land and housing rights seizures in Liberia. Dependency theory is used to analyze the asymmetric relationship between multinational companies and local communities, while human security theory is used to understand the threats faced by individuals in this context. The research findings show that land and housing rights seizures by foreign investors in Liberia can threaten individual security. Multinational companies often exploit vulnerabilities and legal uncertainties to acquire land unfairly, resulting in the loss of housing, livelihoods, and physical security for local communities. The power disparity between companies and local communities is clearly evident, as demonstrated by the negative impacts experienced by the local communities. This research also explores alternative economic models or community-led initiatives in other regions that have successfully ensured fairer economic benefits and sustainable development. These case studies provide valuable insights into how local communities can assert their rights and achieve more equitable economic outcomes, offering potential pathways for Liberia to mitigate the adverse effects of land seizures and promote sustainable development.